PENILAIAN KINESTETIK DALAM SENI TARI - DINNY DEVI TRIANA (Jurnal Evaluasi Pendidikan, 2012)
This research aims to find out the effect of kinesthetic intelligence in arranging a dance on learning of dance composition knowledge are given assessment of performance process and product. This research was conducted at the State University of Jakarta and Indonesia University of Education, Bandung with 40 students as a sample taken through proportional of random sampling with the aim of college students of art of dance in 2 Institute of Teacher’s Education (LPTK) get a chance to be a sample members equally. This research methods used is an quasi experimental method with a 2 x 2 factorial design. The result of research, it’s show that: (1) intelligence of kinesthetic in arranging dance that was given performance assessment of process more higher than performance assessment of product, (2) intelligence of kinesthetic in arranging dance that have group of mastry of knowledge dance composition high, more higher than group of mastry of knowledge dance composition low, (3) there was found an interaction effect between performance assessment methods with mastery of dance composition, (4) intelligence of kinesthetic in arranging a dance for group of mastery of knowledge dance composition high, that was given performance assessment of process more lower than performance assessment of product, (5) intelligence of kinesthetic in arranging a dance for group of mastry of knowledge dance composition low, that was given performance assessment of process more higher than performance assessment of product, (6) intelligence of kinesthetic in arranging a dance that was given assessment performance of process for group of mastery of knowledge dance composition high, more lower than for group of mastery of knowledge dance composition low, and (7) intelligence of kinesthetic in arranging a dance that was given assessment performance of product for group of mastery of knowledge dance composition high, more higher than for group of mastery of knowledge dance composition low.